How can Health Behavior Theory be made more useful for intervention research? - Jeffery Robert W (BMC, 2004)
Abstract Background The present paper expresses the author's views about the practical utility of Health Behavior Theory for health behavior intervention research. The views are skeptical and perhaps even a bit exaggerated. They are, however, also based on 20-plus years of in-the-trenches research focused on improving health behavior practice through research. Discussion The author's research has been theoretically driven and has involved measurement of varying variables considered to be important theoretical mediators and moderators of health behavior. Regretfully, much of this work has found these variables wanting in basic scientific merit. Health Behavior Theory as we have known it over the last 25 years or so has been dominated by conceptualizations of behavior change processes that highlight cognitive decision-making. Although much of health behavior practice targets what people do rather than what they think, the logic of focusing on thoughts is that what people think about is the key to what they will do in the future, and that interventions that can measure and harness those processes will succeed to a greater extent than those that do not. Unfortunately, in the author's experience, the premise of cognitive theories has fallen short empirically in a number of ways. The cognitive schemata favored by most health behavior theories are difficult to measure, they do not predict behavioral outcomes very well, there is little evidence that they cause behavior, and they are hard to change directly. Summary It is suggested that health behavior researchers reconsider their use of these theories in favor of models whose variables are more accessible to observation and experimental manipulation and that most importantly have strong empirical support.